Limiar de recuperação de ovos de Toxocara canis em solo por técnica de centrífugo-flutuação - Xavier, Iara Giordano Rosa (2009)
The purpose of this study was to evaluate the threshold of a technique of centrifuge-flotation used to recovery Toxocara canis eggs from artificially contaminated soil with 1, 3, 5, 10, 25, 50, 100 and 200 eggs. Soil samples were previously sterilized. Aliquots of one gram were contaminated with 20 µL of a solution containing the eggs. For each trial, 10 contaminated samples were tested. Threshold was evaluated based on a centrifuge-flotation technique by using zinc sulphate (Zn2SO4) and sodium nitrate solutions (Na2NO3), specific gravity 1.20. The recovery of eggs was directly proportional to the number of eggs. By using both solutions, it was possible to reach the success in samples containing three eggs. Only Zn2SO4 showed efficacy in soil contaminated with a single egg. The recovery of 100% in all tests was obtained for samples containing 10 and 25 eggs, respectively, for Zn2SO4 and Na2NO3. There was no difference in the mean of recovered eggs both for the efficacy of solutions and for the repetition of evaluations in a same trial. The centrifuge-flotation technique shows efficiency even in samples containing low number of eggs.